1994
DOI: 10.1055/s-2007-994560
|View full text |Cite
|
Sign up to set email alerts
|

Motor and Cardiac Response during Habituation Testing: Demonstration of Exaggerated Cardiac Reactivity in a Subgroup of Normal Human Fetuses

Abstract: In this study we wanted to determine: (1) whether or not a relationship existed between the rate of habituation of the fetal motor response and changes in the fetal heart rate (FHR), and (2) if this relationship could be used to identify a subgroup of fetuses who exhibited exaggerated cardiac reactivity during habituation testing. Thirty-nine normal human fetuses between 34 and 40 weeks of gestation were evaluated. Habituation testing consisted of a 1 second vibroacoustic stimulus with a 10 second interstimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Simultaneous recording of physiological and behavioral data allows for the interrogation of possible linkages in behavior and physiology as well as possible “dissociations.” Recent data suggest that the dissociation of two or more variables that normally occurs together will provide a more sensitive index of pathological conditions and, therefore, provide a more sensitive marker of CNS integrity. 23,53 (3) Real‐time and off‐line analyses can be used effectively for research as both behavioral and physiological data are simultaneously recorded. Off‐line assessment can be used to investigate subtleties not able to be interrogated during real‐time recording.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous recording of physiological and behavioral data allows for the interrogation of possible linkages in behavior and physiology as well as possible “dissociations.” Recent data suggest that the dissociation of two or more variables that normally occurs together will provide a more sensitive index of pathological conditions and, therefore, provide a more sensitive marker of CNS integrity. 23,53 (3) Real‐time and off‐line analyses can be used effectively for research as both behavioral and physiological data are simultaneously recorded. Off‐line assessment can be used to investigate subtleties not able to be interrogated during real‐time recording.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have varied in every aspect of stimulus characteristics and response assessment. While many authors have used VAS to habituate the fetus (Doherty & Hepper, 2000; Groome et al , 1994; Kuhlman et al , 1988; Madison et al , 1986b; van Heteren et al , 2001), there are other studies where pure tones have been used as the habituating stimulus (Hepper & Shahidullah, 1992; Kisilevsky & Muir, 1991). Vibroacoustic stimulation (VAS) does appear to have some advantages over other forms of fetal stimulation: intense stimuli may overcome any effect of behavioural state on fetal responsiveness (Shalev et al , 1990) and VAS has also been reported to produce more reliable responding (Leader, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The criterion for habituation has included ‘non‐response to two consecutive stimuli’ (Kuhlman et al , 1988), ‘non‐response to four consecutive stimuli’ (van Heteren et al , 2001) and ‘non‐response to five consecutive stimuli’ (Doherty & Hepper, 2000; Hepper & Shahidullah, 1992; Leader et al , 1982a; Madison et al , 1986b). Others have employed a ‘rate of change score’ (Groome, Swiber, Bentz, Holland, & Atterbury, 1995), a score on a scale (Groome et al , 1993, 1994) or a ‘movement score’ (Kisilevsky & Muir, 1991). Methods used to evaluate FHR habituation have been even more diverse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations